Pengaruh Influencer dan Content Marketing serta Online Customer Review terhadap Keputusan Pembelian Skincare Bioaqua di TikTok - Ika Ratih Purwanti; Asnawati (Indo Publishing, 2025)
This study aims to determine the influence of influencers, content marketing, and online customer reviews on purchasing decisions for Bioaqua skincare products on TikTok. The background of this research is the increasing use of the internet and the growth of TikTok as a marketing platform, which has transformed consumer behavior in seeking information and making decisions. As a result, digital promotional strategies have become increasingly important for skincare brands. This research employs a quantitative method with a purposive sampling technique. Data were collected through a questionnaire distributed to 120 respondents. The data were analyzed using SmartPLS. The results indicate that the influencer and content marketing variables have a significant influence, whereas online customer reviews do not show a significant effect on purchasing decisions. These findings suggest that consumers are more strongly influenced by influencers and content marketing than by online customer reviews